Criação de uma Framework para Melhorar a Experiência de Jogo através de Biofeedback - José Pedro Pereira Amorim (2017)
In the field of Human-Computer Interaction (HCI), there has been recently a strong interest in new forms of interaction that complement or replace traditional - keyboard and mouse. These new forms of interaction, such as biofeedback with the use of physiological signals, allow players a more immersive experience. Although already investigated the use of biofeedback mechanisms in the context of videogames, and especially the mechanisms of direct biofeedback where players perform actions in the game explicitly, it hasn't been studied the limitations that biofeedback mechanisms have when applied to already existing videogames. The objective of this dissertation is to study the effects of biofeedback mechanisms applied to preexisting commercial videogames - that is, to explore the variety of mechanisms that can be used with the same framework and to understand how the same sensor can serve different mechanics. It is also intended to identify the design and adaptation limitations of this to current games' mechanics. To accomplish this, a framework was developed capable of collecting and interpreting data from several physiological sensors, and provide a simple graphical interface for the configuration of activation rules of the game mechanics. Through the integration of this framework in the videogame Skyrim, it was possible to carry out a study case with 26 participants, where we compared two scenarios, one using traditional interaction and the other physiological interaction. Thus, it was possible to evaluate the impact of these mechanisms of interaction through questionnaires that allowed the evaluation of participants' experience in both scenarios, depending on the degrees of Fun, Usability, Originality, among others. The results of the dissertation allow us to conclude that the biofeedback version proved to be more fun, although the game mechanics in the original version are more user-friendly. The majority of participants gave preference to the videogame with biofeedback. This work highlights the advantages that the application of game mechanics allied to the use of biofeedback can bring to videogames.